PENGARUH KONJAC GLUCOMANAN DARI PORANG TERHADAP PERUBAHAN PERILAKU GANGGUAN JIWA BERAT - Seftiana Putri Widodo; Sugeng Mashudi; Dianita Rifqia Putri (Universitas Muhammadiyah Ponorogo, 2022)
Mental health disorders in the community are one of the problems that still occur in Indonesia, sufferers of severe mental disorders in Indonesia still use antipsychotic drugs in reducing psychotic symptoms of severe mental disorder behavior. Drugs taken by people with severe mental disorders for more than five years cause psychotic symptoms that result in weight gain and high blood glucose levels which will cause metabolic syndrome which makes negative and positive behavior increase in people with severe mental disorders. The purpose of this study was to analyze the effect of Amorphophallus muelleri blume on behavioral changes in severe mental disorders. “The design in this study was experimental with One-group pre-post test with consecutive sampling method, obtained as many as 20 samples of patients with severe mental disorders in Paringan village.” This study was tested using the Wilcoxon test. “The results of the behavioral test using PANSS before the intervention was carried out with a value of 32,9500 and after the intervention the results were relatively low with a value of 22,3000.” Based on the Wilcoxon test, it was found that the p value was 0.000 and 0.000 0.05, so it was concluded that there was a decrease in the behavior of patients with severe mental disorders from being in the moderate category to the mild category. “Thus, it can be stated that there is an effect of konjac glucomanan from porang on improving the behavior of severe mental disorders in Paringan Village, Jenangan. Ponorogo.”Keywords: Amorphophallus Muelleri Blume, Severe Mental Disorder, Metabolic Syndrome, Konjac Glucomannan